Animation and Manga on Improvement in Students' Problem-Solving Capabilities: Comparison of Two Psychometric Models - Ting-Sheng Weng (MDPI AG, 2024)
To improve the problem-solving capabilities of students, this study explored using interactive digital teaching materials based on animation and manga. A classroom teaching system was developed based on teaching material using a manga format. Students from a national university and a science and technology university in southern Taiwan were recruited. A questionnaire survey was administered for data collection. A total of 104 valid samples were collected; the data were analysed using SPSS 17.0. Two statistically significant models could be used to predict learning outcomes, and the highest R2 value was 52.5%. The utilisation of interactive multimedia teaching materials based on animation and manga helped students apply knowledge to solve practical problems, cultivating their problem-solving capabilities. The findings differed from previous studies; models developed in this study could be used to determine the effects and relationships of multiple factors.